2005
DOI: 10.1038/sj.gene.6364246
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of human microglial cells to interferon-γ

Abstract: Microglia, the resident macrophages in the central nervous system (CNS), play a pivotal role in innate and adaptive immune responses in the brain. The immune functions of microglia are regulated by cytokines, including interferon (IFN)-g, which is a major mediator of macrophage activation. We describe the transcriptional profile of human fetal microglial cells at 1, 6, and 24 h after IFN-g treatment. The results show a change in the expression of 405 genes including transcriptionally induced chemokines, IFN-g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 48 publications
3
66
1
1
Order By: Relevance
“…1A) and protein (Fig. 3) levels appears to contradict the previous reports of an up-regulating effect of IFN-␥ on IL-33 mRNA in skin keratinocytes (32,33), cardiac myocytes, and fibroblasts (47), yet it is consistent with the previously observed apparent attenuating effect of IFN-␥ on IL-33 mRNA in macrophages and microglial cells (48,49). To clarify the Th1 and Th2 regulation of the IL-33 protein expression in the complexity of a realistic in vivo environment, AdV-mediated gene delivery was utilized (Fig.…”
Section: Effect Of Proteasome Lmp2 Subunit Inhibition On Ifn-␥-drivencontrasting
confidence: 56%
See 1 more Smart Citation
“…1A) and protein (Fig. 3) levels appears to contradict the previous reports of an up-regulating effect of IFN-␥ on IL-33 mRNA in skin keratinocytes (32,33), cardiac myocytes, and fibroblasts (47), yet it is consistent with the previously observed apparent attenuating effect of IFN-␥ on IL-33 mRNA in macrophages and microglial cells (48,49). To clarify the Th1 and Th2 regulation of the IL-33 protein expression in the complexity of a realistic in vivo environment, AdV-mediated gene delivery was utilized (Fig.…”
Section: Effect Of Proteasome Lmp2 Subunit Inhibition On Ifn-␥-drivencontrasting
confidence: 56%
“…Some evidence suggests an IFN-␥-driven increase in IL-33 mRNA transcription in human skin keratinocytes (32,33), cardiac myocytes, and fibroblasts (47) but not dermal fibroblasts (32,33). By contrast, IFN-␥ appears to attenuate IL-33 mRNA expression in macrophages (48) and microglial cells (49).…”
mentioning
confidence: 99%
“…The detection of CXCL12 in the cerebrospinal fluid of patients without neuroinflammatory diseases indicates that this chemokine does not necessarily promote inflammation within the CNS (28). Indeed, our data would argue that CXCL12 prevents CXCR4-expressing mononuclear cells from penetrating the CNS parenchyma, where they would contribute to microglial activation and demyelination via the actions of inflammatory mediators such as IFN-␥ (59,60). Consistent with this argument, Stumm et al (23) previously reported that the administration of LPS is associated with decreased expression of CXCL12 by CNS endothelial cells, supporting the notion that CXCL12 does not promote activation of the CNS microvasculature.…”
Section: Discussionmentioning
confidence: 94%
“…In microglial cells, IFN-␥ induces changes in the expression level of at least 450 genes encoding chemokines, signaling molecules, and the MHC (17). IFN-␥ also increases microglial responses to A␤ peptides by the production of proinflammatory and neurotoxic mediators (18).…”
Section: A Lzheimer's Disease (Ad)mentioning
confidence: 99%